Diastereoselective Mannich reactions of pseudo-C2-symmetric glutarimide with activated imines - Ishikawa, Tatsuya; Kawasaki-Takasuka, Tomoko; Kubota, Toshio; Yamazaki, Takashi (Beilstein Journal of Organic Chemistry, 2017)
As an extension of the boron enolate-based aldol reactions, the oxazolidinone-installed bisimide 1a from 3-(trifluoromethyl)glutaric acid was employed for Mannich reactions with tosylated imines 2 as electrophiles to successfully obtain the corresponding adducts in a stereoselective manner.
Keywords: chiral oxazolidinones; diastereoselectivity; Mannich reactions; pseudo-C2 symmetry; trifluoromethyl